(untitled) (Eurasian Research Bulletin, 2022)
It can be concluded that sulfo-mineral cements have greater heat resistance than Portland cement and alumina-belite, and it can also be used for the preparation of heat-resistant concrete and prefabricated reinforced concrete structures, since sulfo-aluminate-silicate cements have good adhesion to both mortars and concretes